Investigating Poor Sleep Quality and Associated Factors During the COVID-19 Pandemic: A Population-Based Survey in Bangladesh - Islam, Md. Saiful; Rahman, Md. Estiar; Zubayer, Abdullah Al; Bhuiyan, Md. Rifat Al Mazid; Khan, Md. Kamrul Ahsan; Hossain, Liakat; Sujon, Md. Monjurul Ahasan (Frontiers in Public Health, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has adversely affected the sleep quality of individuals, and is a poorly investigated area. This study aimed to investigate the prevalence estimate of poor sleep quality and its associated factors among Bangladeshi residents during the COVID-19 pandemic. Methods: An online cross-sectional survey was carried out from July 20 to August 5, 2020, involving 975 Bangladeshi residents (male: 54.2%; mean age: 26.7 ± 9.4 years; age range: 18–75 years). A self-reported questionnaire was answered by the respondents, covering information on demographic characteristics, perceived physical health status, COVID-19-related factors, COVID-19-induced anxiety assessment, and sleep quality. To assess sleep quality, the Bangla version of the Pittsburgh Sleep Quality Index was used. Logistic regression models were performed to analyze the factors associated with sleep quality. Results: The prevalence estimate of poor sleep quality was 55.1% among the Bangladeshi people during the COVID-19 pandemic. As per the multiple regression analysis, poor sleep quality was significantly higher among respondents who reported female gender, moderate/poor health status, indirect contact with COVID-19 infected patients, decreased household income due to the COVID-19 pandemic, fear of infection, and COVID-19-induced anxiety. Conclusion: Poor sleep quality was slightly prevalent among general people in Bangladesh during the COVID-19 pandemic. The findings indicate an immediate response for this vulnerable group to improve the sleep quality during the public health emergency of COVID-19.